Handbook of fiber chemistry - Lewin, Menachem, 1918- (CRC/Taylor & Francis, 2007)
'' ... Should be considered a new book rather than just an update of the first edition.''. '' ... this hefty volume offers a world of surprises in its compass, and is well worth the money to mill labs.
Keywords: Textile fibers.; Textile chemistry.; elektronické knihy; electronic books